Correlation Betveen Erythromycin- Resistance Phenotypes ofStreptoco cc us Pne unrc nifi e ancl the Invitro Activitl' of Telith romycineand Azithrornycine - Saleem Mohammed AIi, Nuha (Tikrit Journal of Pharmaceutical Sciences, 2023)
Tow principal mechanisms have so far been found to be responsible for acquired macrolide ,lincosamide and streptogramin B (MLSB) antibiotics resistance in Streptococcus pneumoniae : target site modification and active drug efflux .the target site modification is due to methylase prevents the binding of the antibiotic to its ribosomal target and can be expressed either in a constitutive (cMLS phenotype) or inducible (iMLS phenotype ) manner .the macrolide efflux system,M phenotype ,is mediated by a membrane protein responsible for the efflux resistance. Although the incidence of resistance to macrolides was low in the past today the incidence reported by several countries shows a sensible increase. Thus it is necessary to search and test novel antimicrobial agents characterized by a spectrum of activity against the most common respiratory pathogens. This study compared the invitro activity (MIC and MBC) of telithromycin with activity of azithromycin against Streptococcus pneumoniae recently isolated from San Giovanni Battista Hospital (Turin, Italy). Erythromycin — resistance phenotypes were determined through a triple — disk test to correlate a potential different bacterial pattern to antimicrobial s sceptibility. The incidence of erythromycin-resistance was 26.66% .In the group of Ery-R Streptococcus pneumoniae 58.33% strains belonged to ¢MLS phenotype, 33.33% to M phenotype and 8.33% to iMLS phenotype. Telithromycin presented MIC values lower than those detected with azithromycin against all isolated strains . Telithromycin appeared to be highly active against Streptococcus pneumoniae, in particular when resistance is mediated by the efflux system confirming its clinical efficacy among respiratory streptococcal infections.